2008
DOI: 10.3390/ijms9091561
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Drugs Against Viral Agents

Abstract: Development of antivirals has focused primarily on vaccines and on treatments for specific viral agents. Although effective, these approaches may be limited in situations where the etiologic agent is unknown or when the target virus has undergone mutation, recombination or reassortment. Augmentation of the innate immune response may be an effective alternative for disease amelioration. Nonspecific, broad-spectrum immune responses can be induced by double-stranded (ds)RNAs such as poly (ICLC), or oligonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 202 publications
0
16
0
Order By: Relevance
“…The TLR9 activated PMCs significantly blocked MRSA growth and blocking TLR9 activation nullified this inhibitory response suggesting that CpG induced TLR9 dependent mBD14 may inhibit MRSA. The TLR9 agonists, (the CpG-ODNs) are known to trigger innate immune responses in several immune cells including Natural Killer cells, Dendritic Cells (DCs), and macrophages; and are also known to promote adaptive immune responses, such as Th1 polarization, cytokine release, and inhibition of interferons [8,14]. Moreover, TLR9 has been exploited as the important receptor facilitating the interferon induction in DCs during S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLR9 activated PMCs significantly blocked MRSA growth and blocking TLR9 activation nullified this inhibitory response suggesting that CpG induced TLR9 dependent mBD14 may inhibit MRSA. The TLR9 agonists, (the CpG-ODNs) are known to trigger innate immune responses in several immune cells including Natural Killer cells, Dendritic Cells (DCs), and macrophages; and are also known to promote adaptive immune responses, such as Th1 polarization, cytokine release, and inhibition of interferons [8,14]. Moreover, TLR9 has been exploited as the important receptor facilitating the interferon induction in DCs during S .…”
Section: Discussionmentioning
confidence: 99%
“…TLR signaling contribute to the expression of several inflammatory and antimicrobial genes involved in various pathogenesis including Staphylococcal infections. The CpG-DNA induced TLR9 activation has been demonstrated to provide protection against various infections [8]. The CpG-DNA activation leads to secretion of several cytokines that in turn contribute to non-specific and specific immunity.…”
Section: Introductionmentioning
confidence: 99%
“…A study with mice covering the age range from 4 days to 182 days showed that at day 7 after the CVB3 infection, myocarditis occurred in all of 12-56 day old mice and not in 4-day old mice [3]. Another study with the mice covering the age range from 1 week to 45 weeks demonstrated that 1-3 week old mice were the least susceptible to CVB3-induced myocarditis while [12][13][14][15][16][17][18] week old mice were more susceptible. The variation was correlative with virus concentrations in the heart-tissue.…”
Section: Introductionmentioning
confidence: 93%
“…neutralizing antibody via up-regulating co-stimulatory molecules in antigen presenting cell (APC) such as dendritic cells (DCs) and B cells and promoting proliferation and differentiation of these cells [29,[40][41][42]. Additionally, YW002 could activate TLR9 in B cells, thus providing strong synergy signals to activate B cells to differentiate into plasma cells that secrete higher level of CVB3 neutralizing antibody [13,43]. It has been reported that repeated CpG-ODN administration in normal healthy mice causes serious untoward consequences such as development of multifocal liver necrosis and hemorrhagic ascites [44].…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation